Bi-layer optimal secondary frequency control approach for energy storage clusters considering wind power uncertainty - Wang, Zizhao; Wu, Feng; Li, Yang; Huang, Weidong; Shi, Linjun (Frontiers in Energy Research, 2022)
Increasing penetration of wind power with intermittency and variability threatens the stability of the power system frequency. The fast response capability of the energy storage system (ESS) makes it an effective measure to improve frequency regulation performance. However, designing an optimal control for numerous energy storage units (ESUs) with different power and energy characteristics is challenging. To solve the dilemma that the distributed control methods cannot achieve optimality over time horizons while the centralized optimization methods would cause high computational burdens, a bi-layer optimal control approach is proposed in this study. In the upper layer, a multi-area secondary frequency control (SFC) problem is established to determine control policies for ESS clusters under continuous wind power fluctuations and is solved by the Itô theory-based stochastic optimization (ITB-SO) method with high computational efficiency in a rolling-horizon manner. In the lower layer, the power output of ESUs is dispatched and coordinated using the distributed algorithm (DA) method via communication networks, considering different characteristics and the current state-of-charge (SoC) levels. Simulation studies carried out in a dual-region test system evidence the improvement of system frequency stability by compensating for rapid wind power fluctuations immediately via ESSs. The results show that the proposed ITB-SO method without scenario generation is suitable for real-time SFC for the ESS. The effectiveness of the DA method and its robustness in encountering loss of communication links are also verified.